Hybrid diphosphorus ligands in rhodium catalysed asymmetric hydroformylation - Chikkali, Samir H.; van der Vlugt, Jarl Ivar; Reek, Joost N. H. (Coordination Chemistry Reviews, 2014)
This review aims to illustrate recent advances in the application of hybrid diphosphorus ligands for the Rh catalysed hydroformylation of alkenes, discussing the most prevalent classes of hybrid systems, i.e. phosphine-phosphinite, phosphine-phosphonite, phosphine-phosphite, phosphite-phosphoramidite and phosphite-phosphoramidite and comparing their performance with relevant C-2 symmetric counterparts. In order to introduce the field and put the results in context, a short overview on Rh hydroformylation is provided. Available spectroscopic (in situ) data on the coordination modes of hybrid phosphorus ligands and the catalytic performance of these systems in asymmetric hydroformylation of vinyl arenes are reported. Potential avenues for future research are shortly discussed. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Asymmetric hydroformylation; Catalyst resting state; Hybrid ligand design; In situ spectroscopy; Rhodium

Highly enantioselective Pd-catalyzed synthesis of P-stereogenic supramolecular phosphines, self-assembly, and implication - Koshti, Vijay S.; Mote, Nilesh R.; Gonnade, Rajesh G.; Chikkali, Samir H. (Organometallics, 2015)
Metal-catalyzed asymmetric addition of a secondary phosphine to an aryl halide is one of the most efficient and reliable approaches for the construction of enantiopure carbon phosphorus bonds. An isolated Pd(II) complex (5) catalyzes the carbon phosphorus coupling reaction between tolylphenylphosphine (la) and 3-iodophenylurea (2b), which proceeds with an unprecedented enantiomeric excess (ee) of 97%. The generality of the strategy has been demonstrated by preparing a small library of a new class of P-stereogenic phosphines with an in-built hydrogen bonding motif for the first time. The P-stereogenic phosphines self-assemble on a metal template via deliberately installed hydrogen-bonding motifs and mimic the bidentate ligand coordination. Interestingly, when it was employed in asymmetric hydrogenation, the supramolecular phosphine {1-(3-(phenyl(o-toly)phosphanyl)pheny)ureal} (6b) produced the corresponding hydrogenated product with the highest enantiomeric excess of 99% along with excellent conversion, demonstrating the potential of these enantioenriched P-chirogenic supramolecular phosphines in asymmetric catalysis.

Highly regioselective isomerizing hydroformylation of long-chain internal olefins catalyzed by a rhodium bis(phosphite) complex - Pandey, Swechchha; Chikkali, Samir H. (ChemCatChem, 2015)
The single-step synthesis, coordination behavior, and application of a bis(phosphite) ligand in the isomerizing hydroformylation of internal olefins was investigated. Interestingly, high-pressure NMR spectroscopy investigations revealed unexpected inequivalency of the two phosphorus nuclei, which display bisequatorial coordination of the bis(phosphite) ligand in a trigonal bipyramidal rhodium complex. Upon employment in the isomerizing hydroformylation of the exceedingly challenging plant oil derived substrate methyl oleate, the bis(phosphite) rhodium complex revealed an unprecedented linear selectivity of 75%.
Keywords: alkenes; bis(phosphite)s; Hydroformylation; isomerization; Rhodium

H-Bonding assisted self-assembly of anionic and neutral ligand on metal: a comprehensive strategy to mimic ditopic ligands in olefin polymerization - Mote, Nilesh R.; Patel, Ketan; Shinde, Dinesh R.; Gaikwad, Shahaji R.; Koshti, Vijay S.; Gonnade, Rajesh G.; Chikkali, Samir H. (Inorganic Chemistry, 2017)
Self-assembly of two neutral ligands on a metal to mimic bidentate ligand coordination has been frequently encountered in the recent past, but self-assembly of an anionic ligand on a metal template alongside a neutral ligand remains an elusive target. Such a self-assembly is hampered by additional complexity, wherein a highly negatively charged anion can form intermolecular hydrogen bonding with the supramolecular motif, leaving no scope for self-assembly with neutral ligand. Presented here is the self-association of anionic ligand 3-ureidobenzoic acid (2a) and neutral ligand 1-(3-(diphenylphosphanyl)phenyl)urea (1a) on a metal template to yield metal complex [{COOC6H4-NH(CO)NH2}{Ph2PC6H4NH(CO)NH2}PdMeDMSO] (4a). The identity of 4a was established by NMR and mass spectroscopy. Along the same lines, 3-(3-phenylureido)benzoic acid (2b) and 1-(3-(diphenylphosphanyl)phenyl)-3-phenylurea (1b) self-assemble on a metal template to produce palladium complex [{COOC6H4NH(CO)NHPh}{Ph2PC6H4NH(CO)NHPh}PdMePy] (5c). The existence of 5c was confirmed by Job plot, 1-2D NMR spectroscopy, deuterium labeling, IR spectroscopy, UV-vis spectroscopy, model complex synthesis, and DFT calculations. These solution and gas phase investigations authenticated the presence of intramolecular hydrogen bonding between hydrogen's of 1b and carbonyl oxygen of 2b. The generality of the supramolecular approach has been validated by preparing six complexes from four monodentate ligands, and their synthetic utility was demonstrated in ethylene polymerization. Complex 4a was found to be the most active, leading to the production of highly branched polyethylene with a molecular weight of 55700 g/mol and melting temperature of 112 degrees C.

Hydrogen bonding assissted supramolecular metal catalysis - Mote, Nilesh R.; Chikkali, Samir H. (Chemistry - an Asian Journal, 2018)
The process of catalyst screening and discovery still largely relies on traditional ligand-design approaches, which suffer from complex synthetic requirements and offer limited structural diversity. On the contrary, supramolecular chemistry offers the potential to harness multiple weak secondary interactions to deliver self-assembled catalysts with diverse structures or to orient substrates to achieve enzyme-like activity and selectivity. Herein, the application of hydrogen-bonding (H-bonding) interactions as a construction element and directing group in "supramolecular transition-metal catalysis" is critically reviewed and the current state-of-the-art in the field is presented. H-bonding interactions empower structurally simple ligands to deliver complex self-assembled catalysts, which have been found to catalyze a gamut of organic transformations, including hydroformylation, hydrogenation, and allylation reactions. As we will discuss, on many occasions, these supramolecular catalysts outperform their analogous covalently linked catalytic systems. The potential of H-bonding interactions as directing groups has recently been recognized by the scientific community and this Focus Review presents the role of hydrogen-bonding interactions in directing substrates to obtain excellent selectivities and activities in a range of catalytic transformations

Hydrogen-bonding-assisted supramolecular metal catalysis - Mote, Nilesh R.; Chikkali, Samir H. (Chemistry-An Asian Journal, 2018)
The process of catalyst screening and discovery still largely relies on traditional ligand-design approaches, which suffer from complex synthetic requirements and offer limited structural diversity. On the contrary, supramolecular chemistry offers the potential to harness multiple weak secondary interactions to deliver self-assembled catalysts with diverse structures or to orient substrates to achieve enzyme-like activity and selectivity. Herein, the application of hydrogen-bonding (H-bonding) interactions as a construction element and directing group in "supramolecular transition-metal catalysis" is critically reviewed and the current state-of-the-art in the field is presented. H-bonding interactions empower structurally simple ligands to deliver complex self-assembled catalysts, which have been found to catalyze a gamut of organic transformations, including hydroformylation, hydrogenation, and allylation reactions. As we will discuss, on many occasions, these supramolecular catalysts outperform their analogous covalently linked catalytic systems. The potential of H-bonding interactions as directing groups has recently been recognized by the scientific community and this Focus Review presents the role of hydrogen-bonding interactions in directing substrates to obtain excellent selectivities and activities in a range of catalytic transformations.

Highly enantioselective synthesis of sitagliptin - Khopade, V. Kishor; Sen, Anirban; Birajdar, Rajkumar S.; Paulbudhe, Uday P.; Kavale, Dattatry S.; Shinde, Prashant S.; Mhaske, Santosh B.; Chikkali, Samir H. (Asian Journal of Organic Chemistry, 2020)
A highly enantioselective synthesis of sitagliptin, a potent DPP-4 inhibitor, is reported. Explicitly identified chiral FerroLANE ligands in the presence of rhodium catalyze the asymmetric hydrogenation of an enamine to yield sitagliptin with excellent enantioselectivity (98% ee). The process was scaled up to 5 g and the final product was isolated as a phosphate salt with >99% ee.
Keywords: asymmetric hydrogenation; catalysis; FerroLANE ligands; Rhodium; sitagliptin

Hydroformylation of olefins by metals other than rhodium - Kumar, Rohit; Chikkali, Samir H. (Journal of Organometallic Chemistry, 2022)
Metal catalyzed hydroformylation of alkenes is an atom economic transformation to construct useful aldehydes and is being industrially practiced for decades. The most commonly used metal for this transformation on an industrial scale is rhodium. However, rhodium is rare, costly, and is depleting at a skyrocketing rate. Therefore, finding a suitable alternative to rhodium for metal-catalyzed hydroformylation has been on the radar of many academic and industrial researchers. This review presents the scientific advancements reported in the hydroformylation reaction using metals other than rhodium. An overview of recent progress in palladium, iridium, ruthenium, cobalt, platinum, and iron-catalyzed hydroformylation is presented. Hydroformylation of alkenes and alkynes, using syngas as well as syngas surrogates is examined. The evaluation of the current status of non-rhodium metals in hydroformylation suggests that the field is still in a nascent stage and, except cobalt, no other metal poses a significant challenge to the dominance of rhodium. Deep mechanistic understanding of rate-limiting elementary steps in the non-rhodium metals is largely missing and thus only limited success is reported. Intense research on ligand design, mechanistic understanding, and choice of non-rhodium metal precursors may change this scenario in near future.
Keywords: aldehydes; alkenes; catalysis; Hydroformylation; Non-rhodium metals